Do Institutional Distances Influence South-South Cross-Border Acquisitions? - Moura, Stephanie Tonn Goulart; Krug, Juliano; Falaster, Christian; Parisotto, Iara Regina dos Santos (Internext, 2019)
Different countries have different institutional environments. In this way, multinational companies must deal with the difficulties imposed by the differences between their home environment and that of the country where they are inserted. In this article, we analyze the effects of institutional distance on South-South acquisitions. Specifically, we analyze the effect of institutional distance on the amount of participation chosen in Latin American international acquisitions in Brazil. More specifically, the effect of institutional distance is analyzed through the percentage of shares acquired in international acquisitions. Our results contribute to the theory in international business because it explains why Latin American companies prefer to make total acquisitions even in situations of high institutional distances.